The Cooking Content Effect in Instagram to Followers' Satisfaction - Muhammad Agil Kuncoro; Vina Mahdalena; Rini Riyantini (LONTAR: Jurnal Ilmu Komunikasi, 2024)
The tendency for cooking videos to have a long duration to showcase cooking demonstrations is a challenge for Instagram @pattygurlz, as the platform limits the duration to 90 seconds. In addition, in @pattygurlz's Instagram videos, there is no physical appearance of the presenter. This situation is a challenge to persuade Instagram users to be interested in the content. This study aims to identify and analyze the impact of @pattygurlz content on follower satisfaction. This study uses the Uses and gratification theory, where audiences are considered as active voters, evaluating media that can meet their needs. This research uses a quantitative approach with a survey method. The population of this study were Instagram followers @pattygurlz with a sample size of 100. In analyzing the data, researchers conducted validity tests, reliability tests, correlation tests, regression tests, detemination coefficients, and hypothesis tests. The data testing technique is processed using the SPSS version 26 program. The results showed a significant relationship between cooking content and followers' satisfaction. The coefficient of determination shows that 42.9% of followers' satisfaction is influenced by content, while the rest is influenced by other factors.